School Satisfaction in Immigrant and Chilean Students: The Role of Prejudice and Cultural Self-Efficacy - Mera-Lemp, María José; Bilbao, Marian; Basabe, Nekane (Frontiers in Psychology, 2020)
Latin-American immigration has transformed Chilean schools into new multicultural scenarios. Studies about intergroup dynamics among students from different cultural backgrounds and their psychological consequences are still limited in south–south migration contexts. Literature has suggested that intergroup relations influence students’ satisfaction with school, and they could be improved by the development of competences to cope with cultural differences. This study aims to verify if cultural self-efficacy and its dimensions mediated the influence of prejudice on satisfaction with school, in a sample composed by N = 690 Chilean and Latin-American immigrant secondary students. Results showed that cultural self-efficacy reduced the effect of prejudice in satisfaction with school, in the cases of both immigrant and Chilean students. The dimensions of cultural self-efficacy in processing information from other cultures and mixing with different others make the difference. Findings’ contributions for the understanding of adolescents’ intergroup relations and psychosocial interventions at school are discussed.